Low-oxygen titanium and preparation method thereof
Through the method of segmented heating and spheroidization treatment, the problems of high cost and low purity of titanium preparation were solved, the efficient preparation of low-oxygen titanium was achieved, and the performance and economic benefits of the material were improved.
Patent Information
- Application Number
- CN202511240174.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-09-02
- Publication Date
- 2025-10-03
- Estimated Expiration
- 2045-09-02
AI Technical Summary
Existing titanium preparation methods are costly, low in purity, and prone to forming an oxide layer, which results in a decrease in material performance and makes it difficult to be widely used.
The reduction reaction is carried out in a mixed atmosphere of argon and hydrogen using a segmented heating method, combined with mechanical grinding and spheroidization treatment, and stearic acid-nano calcium carbonate core-shell material as a buffer material to control the decomposition and oxidation risks of the reducing agent and improve the purity of titanium powder and spheroidization efficiency.
It reduces production costs, improves the purity and performance of low-oxygen titanium, reduces the formation of oxide layers, and improves the ductility and fracture toughness of the material.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of titanium preparation, and in particular to low-oxygen titanium and a preparation method thereof. Background Art
[0002] Titanium and its alloys are widely used in aerospace, marine, military, and biomedical fields due to their low density, high specific strength, strong biocompatibility, low Young's modulus, strong corrosion resistance, good antibacterial properties, wide operating temperature range, and excellent weldability. As is well known, titanium and its alloys are most widely used in aerospace. However, due to its high reactivity, titanium easily forms surface oxide layers, such as titanium dioxide (TiO2). The increased interstitial oxygen content further triggers the "oxygen embrittlement effect," significantly reducing the ductility and fracture toughness of titanium alloys. Furthermore, the high extraction and production costs of titanium severely restrict its application in a wider range of fields.
[0003] At the same time, the existing magnesium thermal reduction method uses a large amount of chlorine as a raw material in the preparation process, and the reduction reaction must be carried out under high temperature and closed conditions. The reaction conditions are relatively harsh, resulting in high production costs. When calcium or rare earth metals are used for reduction, the amount used is large and the reaction time is long, further increasing production costs. Therefore, it is urgent to prepare and develop a low-oxygen titanium and preparation method with safe production process, low production cost, and higher purity. Summary of the Invention
[0004] One purpose of the present application is to provide a low-oxygen titanium and a preparation method thereof, which is conducive to improving the purity of the low-oxygen titanium, reducing the oxygen content of the low-oxygen titanium product, and improving the safety during the preparation process.
[0005] Another object of the present application is to provide a low-oxygen titanium and a preparation method thereof, which is conducive to reducing production costs, increasing environmental friendliness, and further improving economic benefits.
[0006] To achieve the above objectives, the technical solution adopted in this application is: a method for preparing low-oxygen titanium, comprising the steps of: S100, heating an oxygen-containing titanium source and a metal reducing agent in a mixed atmosphere of argon and hydrogen in stages to react to obtain a first mixture, and placing the first mixture in a vacuum environment after the reaction is completed and then placing it in an argon atmosphere, wherein the size of the titanium source is ≥60 μm, the size of the metal reducing agent is ≤10 mm, and the size is ≥1 mm, and the reducing property of the metal reducing agent is greater than that of elemental titanium; S200, separating products with a size of less than 1 mm from the first mixture to obtain a second mixture; S300, grinding the second mixture in an argon atmosphere to obtain a third mixture with a size of 1 μm to 60 μm; S400, introducing a buffer material into the third mixture in an argon atmosphere to obtain a fourth mixture having a size of ≤25 μm through spheroidization; S500, performing dehydrogenation treatment on the fourth mixture to obtain low-oxygen titanium.
[0007] In some embodiments, step S100 further includes: S110, heating the oxygen-containing titanium source and the metal reducing agent to 180° C. to 250° C., wherein the flow rate of hydrogen is 1.5 L / min to 2.5 L / min, and the ratio of the flow rate of argon to the flow rate of hydrogen is (0.2 to 0.8):1, and reacting for 0.5 h to 1.5 h to obtain a first reactant; S120, heating the first reactant to 250° C. to 350° C., wherein the flow rate of hydrogen is 0.5 L / min to 2.0 L / min, and the ratio of the flow rate of argon to the flow rate of hydrogen is (0.5 to 1):1, and reacting for 0.5 h to 2 h to obtain a second reactant; S130, heating the second reactant to 350° C. to 550° C., wherein the flow rate of hydrogen is 0.5 L / min to 1.2 L / min, and the ratio of the flow rate of argon to the flow rate of hydrogen is (0.8 to 1.2):1, and reacting for 0.5 h to 1.5 h to obtain a third reactant; S140, heating the third reactant to 450°C~900°C, at which time the flow rate of hydrogen is 0.1L / min~0.5L / min, and the ratio between the flow rate of argon and the flow rate of hydrogen is (2~4):1, and the first mixture is obtained after the reaction is carried out for 0.5h~1.5h.
[0008] In some embodiments, step S300 further includes: S310, grinding the second mixture in an argon atmosphere to obtain a first crushed product having a size no greater than 80 μm; S320, placing the first crushed product in an argon flow at a temperature of 150° C. to 200° C. and a flow rate of 100 m / s to 500 m / s for jet milling to obtain a second crushed product; S330 , re-transporting the products with a size greater than 60 μm in the second crushed products to the second mixture in step S200 through a cyclone separator, and the products with a size less than or equal to 60 μm are the third mixture.
[0009] In some embodiments, the metal reducing agent is a hydride of an active metal; the active metal is one or more of potassium, calcium, sodium, and magnesium.
[0010] In some embodiments, step S400 further includes: S410, in an argon atmosphere, adding a buffer material and grinding balls to the third mixture, wherein the grinding ball rotation speed is 150 rpm to 350 rpm, the spheroidization temperature is ≤ 40° C., and the spheroidization time is 1 hour to 4 hours to obtain a third crushed product; S420, heating the third crushed product to 500° C. to 900° C. in an argon atmosphere to obtain a fourth reactant; S430. In an argon atmosphere, the fourth reactant is placed in a dilute hydrochloric acid solution for washing. The washing treatment temperature is 10° C. to 60° C., and the washing treatment time is 5 min to 10 min. The fourth mixture is obtained after drying.
[0011] In some embodiments, the buffer material is a stearic acid-nano calcium carbonate core-shell material, the mass ratio of the buffer material to the third mixture is (0.010~0.015):1, the mass ratio of the third mixture to the grinding balls is 1:(5.0~9.0), and the mass fraction of hydrogen chloride in the dilute hydrochloric acid is ≤5% (wt.%).
[0012] In some embodiments, the preparation method of the stearic acid-nano calcium carbonate core-shell material comprises the steps of: A100, ultrasonically treat the dried nano-calcium carbonate in anhydrous ethanol for 10 min to 30 min to obtain a first solution, and dissolve stearic acid in anhydrous ethanol and stir to form a second solution; A200, under alkaline conditions, adding the second solution to the first solution, heating and stirring, and separating to obtain a fifth mixture; A300, washing the fifth mixture with anhydrous ethanol and drying the mixture at a temperature of 50° C. to 80° C. to obtain a stearic acid-nano calcium carbonate core-shell material.
[0013] In some embodiments, the temperature of the grinding process in step S310 is ≤ 40°C.
[0014] In some embodiments, the step S500 further includes: performing a dehydrogenation treatment on the fourth mixture in a vacuum at 200° C. to 400° C. to obtain low-oxygen titanium.
[0015] In order to achieve the above objectives, the present application also provides low-oxygen titanium prepared by the aforementioned preparation method.
[0016] Compared with the prior art, the present invention has the following advantages: (1) This application reduces the risk of metal reducing agent decomposition by heating the oxygen-containing titanium powder and the metal reducing agent in stages, thereby further reducing the oxygen content of the low-oxygen titanium product. At the same time, hydrogen and argon with different flow rate ratios are used in different stages of the staged heating. In the low-temperature stage, it is beneficial to activate the metal reducing agent and inhibit its premature decomposition, preferentially reduce the oxygen-containing titanium powder and form surface oxygen vacancies, increase the specific surface area, and provide a diffusion channel for subsequent deep deoxidation. In the medium-temperature stage, the oxygen-containing titanium powder is deeply deoxidized and the generation of titanium hydride is suppressed. In the high-temperature stage, the argon flow rate is high, which can take away some by-products and further avoid hydrogen embrittlement.
[0017] (2) This application uses a stearic acid-nano calcium carbonate core-shell material as a buffer material for spheroidization. The long-chain alkyl group in the stearic acid can significantly reduce the friction coefficient between titanium powder particles, reduce the risk of cold welding, and help reduce energy consumption during spheroidization, further improving the spheroidization rate of titanium powder. On the other hand, using nano calcium carbonate with good mechanical properties as a core material can roll in the gaps between titanium powders during the spheroidization process, which is conducive to dispersing local stress, thereby enhancing the spheroidization effect and improving the performance of low-oxygen titanium. DETAILED DESCRIPTION
[0018] Below, the present application is further described in conjunction with specific implementation methods. It should be noted that, under the premise of no conflict, the various embodiments or technical features described below can be arbitrarily combined to form new embodiments.
[0019] As used herein, the term "prepared from" is synonymous with "comprising." As used herein, the terms "comprising," "including," "having," "containing," or any other variations thereof, are intended to cover a non-exclusive inclusion. For example, a composition, process, method, article, or apparatus that comprises a list of elements is not necessarily limited to only those elements but may include other elements not expressly listed or inherent to such composition, process, method, article, or apparatus.
[0020] When an amount, concentration or parameter is expressed as a range, a preferred range, or a range defined by a series of upper preferred values and lower preferred values, this should be understood to specifically disclose the range formed by any pairing of any range upper limit or preferred value with any range lower limit or preferred value, regardless of whether the range is disclosed alone. For example, when a range of "1 to 5" is disclosed, the described range should be interpreted as including the range "1 to 4", "1 to 3", "1 to 2 and 4 to 5", "1 to 3 and 5", etc. When a numerical range is described in this article, unless otherwise stated, the range includes its end values and all integers and fractions within the range.
[0021] Approximating terms in the specification and claims are used to modify a quantity to indicate that the invention is not limited to that specific quantity and includes acceptable modifications close to that quantity that do not result in a change in the relevant basic function. Accordingly, the use of "about," "approximately," or the like to modify a numerical value indicates that the invention is not limited to that exact numerical value. In some instances, approximating terms may correspond to the precision of the instrument used to measure the value. In the specification and claims of this application, range definitions may be combined and / or interchanged, and unless otherwise indicated, such ranges include all subranges contained therein.
[0022] To achieve the above objectives, the technical solution adopted in this application is: a method for preparing low-oxygen titanium, comprising the steps of: S100, heating an oxygen-containing titanium source and a metal reducing agent in a mixed atmosphere of argon and hydrogen in stages to react to obtain a first mixture, and placing the first mixture in a vacuum environment after the reaction is completed and then placing it in an argon atmosphere, wherein the size of the titanium source is ≥60 μm, the size of the metal reducing agent is ≤10 mm, and the size is ≥1 mm, and the reducing property of the metal reducing agent is greater than that of elemental titanium; S200, separating products with a size less than 1 mm from the first mixture to obtain a second mixture; S300, grinding the second mixture in an argon atmosphere to obtain a third mixture with a size of 1 μm to 60 μm; S400, introducing a buffer material into the third mixture in an argon atmosphere to obtain a fourth mixture having a size of ≤25 μm through spheroidization; S500, performing dehydrogenation treatment on the fourth mixture to obtain low-oxygen titanium.
[0023] In the present application, the oxygen-containing titanium source is reduced by segmented heating in a mixed atmosphere of hydrogen and argon, which is conducive to the preparation of high-purity low-oxygen titanium. On the one hand, since the size of the oxygen-containing titanium source and the intermediate product after reduction is smaller than the size of the metal reducing agent, and the difference between the sizes is large, physical methods can be used for separation and screening, which is conducive to reducing the difficulty of separation and further increasing the purity of subsequent products. On the other hand, since the grinding and spheroidization steps are both carried out in an argon atmosphere, while reducing production costs, it prevents the reduced titanium from being re-oxidized and reduces the risk of producing titanium hydride. At the same time, the argon gas obtained after separation of the collected waste gas can be reused in the production process. It is understandable that the grinding process can provide a material with a more uniform size distribution for the spheroidization process, thereby improving the processing efficiency of the spheroidization process. It is worth mentioning that by using a buffer material to spheroidize the third mixture in the spheroidization process, the risk of cold welding is reduced, which is conducive to reducing energy consumption during the spheroidization process and further improving the spheroidization rate of titanium powder.
[0024] In some embodiments, step S100 further includes: S110, heating the oxygen-containing titanium source and the metal reducing agent to 180° C. to 250° C., wherein the flow rate of hydrogen is 1.5 L / min to 2.5 L / min, and the ratio of the flow rate of argon to the flow rate of hydrogen is (0.2 to 0.8):1, and reacting for 0.5 h to 1.5 h to obtain a first reactant; S120, heating the first reactant to 250° C. to 350° C., wherein the flow rate of hydrogen is 0.5 L / min to 2.0 L / min, and the ratio of the flow rate of argon to the flow rate of hydrogen is (0.5 to 1):1, and reacting for 0.5 h to 2 h to obtain a second reactant; S130, heating the second reactant to 350° C. to 550° C., wherein the flow rate of hydrogen is 0.5 L / min to 1.2 L / min, and the ratio of the flow rate of argon to the flow rate of hydrogen is (0.8 to 1.2):1, and reacting for 0.5 h to 1.5 h to obtain a third reactant; S140. Heat the third reactant to 450°C~900°C. At this time, the flow rate of hydrogen is 0.1L / min~0.5L / min, and the ratio between the flow rate of argon and the flow rate of hydrogen is (2~4):1. After reacting for 0.5h~1.5h, a first mixture is obtained.
[0025] It is understandable that the use of hydrogen and argon with different flow rate ratios in different stages of segmented heating is beneficial to activating the metal reducing agent and inhibiting its premature decomposition in the low temperature stage. Furthermore, the active hydrogen atoms can also preferentially reduce the oxygen-containing titanium powder and form oxygen vacancies on its surface, increase the specific surface area, and provide a diffusion channel for subsequent deep deoxidation. On the other hand, to ensure the effective progress of the reduction reaction, the introduction of a large amount of hydrogen can keep the metal reducing agent highly active, and is conducive to maintaining an oxygen-free environment, further increasing the reaction degree of the reduction reaction. The medium temperature stage is to deeply deoxidize the first reactant and the second reactant and inhibit the production of titanium hydride, thereby increasing the flow rate of argon to balance the reduction rate and inhibit the production of side reactions. In the medium and high temperature stages, the reduction reaction is about to end. In order to prevent excess hydrogen from forming titanium hydride with titanium and thus increase the rate of argon introduction, the phenomenon of grain coarsening due to local overheating can also be avoided. In the high-temperature stage, the argon flow rate is higher than the hydrogen flow rate. At this time, a trace amount of hydrogen maintains the activity of the reduced titanium surface, promotes the diffusion of lattice oxygen to the surface and combines with the metal reducing agent. The high flow rate of argon can also take away some by-products, further avoiding hydrogen embrittlement.
[0026] It is worth mentioning that in the later stage of the reduction reaction, the argon content in the system is greater than the hydrogen content, and the subsequent grinding process needs to be carried out in an argon environment. Therefore, when the atmosphere is changed in the later stage of the reduction reaction, the increased argon flow rate is conducive to the rapid change of the system atmosphere, thereby improving production efficiency and operational safety.
[0027] In some embodiments, step S300 further includes: S310, grinding the second mixture in an argon atmosphere to obtain a first crushed product having a size no greater than 80 μm; S320, placing the first crushed product in an argon flow at a temperature of 150° C. to 200° C. and a flow rate of 100 m / s to 500 m / s for jet milling to obtain a second crushed product; S330 , re-transporting products with a size greater than 60 μm in the second crushed products to the second mixture in step S200 through a cyclone separator, and products with a size less than or equal to 60 μm are the third mixture.
[0028] By mechanically grinding and jet milling the preliminarily reduced second mixture, titanium powder can be finely refined in an oxygen-free environment, facilitating the production of titanium powder with a low oxygen content. Notably, mechanical grinding provides the jet mill with a uniformly distributed first crushed product, facilitating a more uniformly distributed product through jet milling. Furthermore, because the system atmosphere is argon, the surface of the newly milled titanium is immediately protected by the argon, thereby reducing the oxygen content in the second crushed product.
[0029] It can be understood that the second crushed product obtained by the air flow milling treatment is then screened out by cyclone separation to remove the product of appropriate size, and the large-sized titanium powder is re-transferred to the grinding step for further processing, which is conducive to obtaining titanium powder products of uniform size and further improving the performance of the low-oxygen titanium product.
[0030] In some embodiments, the metal reducing agent is a hydride of an active metal; the active metal is one or more of potassium, calcium, sodium, and magnesium. It is worth noting that when a metal hydride is used as a reducing agent, since the reduction reaction occurs at elevated temperatures, some of the metal hydride can also serve as a hydrogen source, releasing hydrogen gas. This further reduces hydrogen usage, lowers production costs, and thus increases economic benefits.
[0031] In some embodiments, step S400 further includes: S410, in an argon atmosphere, adding a buffer material and grinding balls to the third mixture, with the grinding ball speed being 150 rpm to 350 rpm, the spheroidization temperature being ≤ 40° C., and the spheroidization time being 1 h to 4 h, to obtain a third crushed product; S420, heating the third crushed product to 500° C. to 900° C. in an argon atmosphere to obtain a fourth reactant; S430. In an argon atmosphere, the fourth reactant is placed in a dilute hydrochloric acid solution for washing. The washing temperature is 10° C. to 60° C., and the washing time is 5 min to 10 min. After drying, a fourth mixture is obtained.
[0032] It should be understood that low-temperature spheroidization helps balance spheroidization efficiency and suppress cold welding. Furthermore, low-temperature treatment enhances the stability of the buffer material and reduces its decomposition risk. Furthermore, heating the third crushed product decomposes at least a portion of the buffer material and remaining impurities. Acid washing then removes non-target products, thereby increasing the purity of the suboxygen titanium in the resulting fourth mixture.
[0033] In some embodiments, the buffer material is a stearic acid-nano-calcium carbonate core-shell material, with the mass ratio of the buffer material to the third mixture being (0.010-0.015):1, the mass ratio of the third mixture to the grinding balls being 1:(5.0-9.0), and the mass fraction of hydrogen chloride in the dilute hydrochloric acid being ≤5% (wt.%). It is worth noting that the buffer material, made by coating the nano-calcium carbonate with stearic acid, comprises a core composed of nano-calcium carbonate that enhances grinding efficiency during spheroidization, dissipates collision stress, and further suppresses cold welding. The shell composed of stearic acid enhances lubrication and stress buffering. In other words, since the spheroidization process is performed at low temperatures, the risk of deformation or even decomposition of the stearic acid in the shell is reduced.
[0034] In some embodiments, the preparation method of stearic acid-nano calcium carbonate core-shell material comprises the steps of: A100, ultrasonically treat the dried nano-calcium carbonate in anhydrous ethanol for 10 min to 30 min to obtain a first solution, and dissolve stearic acid in anhydrous ethanol and stir to form a second solution; A200, under alkaline conditions, adding the second solution to the first solution, heating and stirring, and separating to obtain a fifth mixture; A300. Wash the fifth mixture with anhydrous ethanol and dry it at a temperature of 50° C. to 80° C. to obtain a stearic acid-nano calcium carbonate core-shell material.
[0035] Through appropriate preparation steps, the obtained stearic acid-nano calcium carbonate core-shell material has good performance and, when used in a spheroidization process, enhances the performance and size uniformity of the obtained low-oxygen titanium.
[0036] In some embodiments, the temperature of the grinding process in step S310 is ≤40°C. It should be understood that grinding at low temperatures can not only reduce the risk of cold welding and suppress plastic deformation, but also reduce the generation of titanium hydride. Among them, when titanium hydride decomposes or absorbs hydrogen again, hydrogen is released into the titanium matrix in an atomic state, thereby triggering hydrogen embrittlement, which significantly reduces the impact toughness of the product. Therefore, reducing the risk of titanium hydride generation is conducive to reducing the difficulty of post-processing and further improving the purity of low-oxygen titanium.
[0037] In some embodiments, step S500 further includes: performing a dehydrogenation treatment on the fourth mixture in a vacuum at 200° C. to 400° C. to obtain low-oxygen titanium. The dehydrogenation treatment is completed in a one-step process, and no additional pollutants are generated during the entire process, thus being environmentally friendly.
[0038] To achieve the above objectives, the present application also provides low-oxygen titanium prepared by the aforementioned preparation method. The preparation method provided by the present application can produce low-oxygen titanium with high purity and good performance.
[0039] Example 1 A method for preparing low-oxygen titanium comprises the following steps: (1) 100 g of an oxygen-containing titanium source and 2 g of calcium hydride were heated to 220° C., at which time the flow rate of hydrogen was 2.0 L / min, and the ratio of the flow rate of argon to the flow rate of hydrogen was 0.6:1. After reacting for 1.0 h, a first reactant was obtained; the first reactant was heated to 320° C., at which time the flow rate of hydrogen was 1.2 L / min, and the ratio of the flow rate of argon to the flow rate of hydrogen was 0.6:1. After reacting for 1.5 h, a second reactant was obtained; the second reactant was heated to 500° C., at which time the flow rate of hydrogen was 0.9 L / min, and the ratio of the flow rate of argon to the flow rate of hydrogen was 1:1. After reacting for 1.0 h, a third reactant was obtained; the third reactant was heated to 800° C., at which time the flow rate of hydrogen was 0.3 L / min, and the ratio of the flow rate of argon to the flow rate of hydrogen was 3:1. After reacting for 1.0 h, a first mixture was obtained.
[0040] (2) Physically screening the first mixture to obtain products with a size of less than 1 mm to obtain a second mixture.
[0041] (3) Grinding the second mixture in an argon atmosphere to obtain a first crushed product with a size not greater than 80 μm; placing the first crushed product in an argon flow at a temperature of 180°C and a flow rate of 300 m / s for air flow milling to obtain a second crushed product; and re-transferring the product with a size greater than 60 μm in the second crushed product to the second mixture through a cyclone separator, and the product with a size ≤60 μm is the third mixture.
[0042] (4) In an argon atmosphere, 0.8 g of stearic acid-nano calcium carbonate core-shell material and grinding balls were added to the third mixture at a grinding ball speed of 280 rpm, a spheroidization temperature of 20°C, and a spheroidization time of 3 h to obtain a third crushed product; in an argon atmosphere, the third crushed product was heated to 850°C to obtain a fourth reactant; in an argon atmosphere, the fourth reactant was placed in a dilute hydrochloric acid solution with a mass fraction of 3% (wt.%) of hydrogen chloride for washing at a washing temperature of 20°C and a washing time of 8 min, and dried to obtain a fourth mixture.
[0043] (5) The hydrogen in the fourth mixture is removed in a vacuum at 300° C. to obtain low-oxygen titanium.
[0044] Example 2 The difference between Example 2 and Example 1 is that in step (1), 100 g of oxygen-containing titanium source and 2 g of magnesium hydride are heated to 220°C.
[0045] Example 3 The difference between Example 3 and Example 1 is that in step (1), 100 g of oxygen-containing titanium source and 2 g of elemental magnesium are heated to 220°C.
[0046] Example 4 The difference between Example 4 and Example 1 is that step (1) is: heating 100 g of an oxygen-containing titanium source and 2 g of calcium hydride to 220° C., at which time the flow rate of hydrogen is 2.0 L / min, and the ratio between the flow rate of argon and the flow rate of hydrogen is 0.4:1, and reacting for 1.0 h to obtain a first reactant; heating the first reactant to 320° C., at which time the flow rate of hydrogen is 1.2 L / min, and the ratio between the flow rate of argon and the flow rate of hydrogen is 0.4: 1. After reacting for 1.5 hours, a second reactant is obtained; the second reactant is heated to 500° C., at which time the flow rate of hydrogen is 0.9 L / min, and the ratio of the flow rate of argon to the flow rate of hydrogen is 0.6:1, and after reacting for 1.0 hour, a third reactant is obtained; the third reactant is heated to 800° C., at which time the flow rate of hydrogen is 0.3 L / min, and the ratio of the flow rate of argon to the flow rate of hydrogen is 1:1, and after reacting for 1.0 hour, a first mixture is obtained.
[0047] Example 5 The difference between Example 5 and Example 1 is that step (1) is: heating 100 g of an oxygen-containing titanium source and 2 g of calcium hydride to 220° C., at which time the flow rate of hydrogen is 2.0 L / min, and the ratio between the flow rate of argon and the flow rate of hydrogen is 0.8:1, and reacting for 1.0 h to obtain a first reactant; heating the first reactant to 320° C., at which time the flow rate of hydrogen is 1.2 L / min, and the ratio between the flow rate of argon and the flow rate of hydrogen is 0.8: 1. After reacting for 1.5 hours, a second reactant is obtained; the second reactant is heated to 500° C., at which time the flow rate of hydrogen is 0.9 L / min, and the ratio of the flow rate of argon to the flow rate of hydrogen is 1.2:1, and after reacting for 1.0 hour, a third reactant is obtained; the third reactant is heated to 800° C., at which time the flow rate of hydrogen is 0.3 L / min, and the ratio of the flow rate of argon to the flow rate of hydrogen is 4:1, and after reacting for 1.0 hour, a first mixture is obtained.
[0048] Example 6 The difference between Example 6 and Example 1 is that the buffer material in step (4) is polypropylene.
[0049] Example 7 The difference between Example 7 and Example 1 is that the buffer material in step (4) is nano-calcium carbonate.
[0050] Comparative Example 1 The difference between Comparative Example 1 and Example 1 is that no buffer material is used in step (4).
[0051] Comparative Example 2 The difference between Comparative Example 2 and Example 1 is that the flow rate ratio of hydrogen to argon in the gas atmosphere in step (1) is constant at 1:1.
[0052] Comparative Example 3 The difference between Comparative Example 3 and Example 1 is that the flow rate ratio of hydrogen to argon in the gas atmosphere in step (1) is constant at 0.5:1.
[0053] Comparative Example 4 The difference between Comparative Example 4 and Example 1 is that the flow rate ratio of hydrogen to argon in the gas atmosphere in step (1) is constant at 1.5:1.
[0054] Performance Testing The low-oxygen titanium prepared in Examples 1 to 7 and Comparative Examples 1 to 4 was tested using a pulsed melt oxygen analysis method and a scanning electron microscope. The test results are shown in Table 1.
[0055] Table 1: Performance test of low oxygen titanium
[0056] As shown in Examples 1 through 3 in Table 1, selecting an appropriate metal reducing agent facilitates the production of uniformly distributed, high-purity suboxygen titanium. Furthermore, Examples 1 and 4 through 5 demonstrate that using different flow rate ratios of hydrogen and argon at different stages of the reduction reaction enhances the degree of reduction of the oxygen-containing titanium powder and further reduces the oxygen content in the suboxygen titanium.
[0057] It can be understood that by grinding titanium powder with a suitable buffer material, low-oxygen titanium with good uniformity in use can be produced.
[0058] The above describes the basic principles, main features, and advantages of the present application. Those skilled in the art should understand that the present application is not limited to the above-described embodiments. The above-described embodiments and the specification merely illustrate the principles of the present application. Various changes and improvements may be made to the present application without departing from the spirit and scope of the present application. These changes and improvements fall within the scope of the present application for which protection is sought. The scope of protection claimed by the present application is defined by the appended claims and their equivalents.
Claims
1. A method for preparing low-oxygen titanium, characterized in that: Including steps: S100, heating an oxygen-containing titanium source and a metal reducing agent in a mixed atmosphere of argon and hydrogen in stages to react to obtain a first mixture, and placing the first mixture in a vacuum environment after the reaction is completed and then placing it in an argon atmosphere, wherein the size of the titanium source is ≥60 μm, the size of the metal reducing agent is ≤10 mm, and the size is ≥1 mm, and the reducing property of the metal reducing agent is greater than that of elemental titanium; S200, separating products with a size of less than 1 mm from the first mixture to obtain a second mixture; S300, grinding the second mixture in an argon atmosphere to obtain a third mixture with a size of 1 μm to 60 μm; S400, introducing a buffer material into the third mixture in an argon atmosphere to obtain a fourth mixture having a size of ≤25 μm through spheroidization; S500, performing dehydrogenation treatment on the fourth mixture to obtain low-oxygen titanium.
2. The preparation method according to claim 1, characterized in that The step S100 further includes: S110, heating the oxygen-containing titanium source and the metal reducing agent to 180° C. to 250° C., wherein the flow rate of hydrogen is 1.5 L / min to 2.5 L / min, and the ratio of the flow rate of argon to the flow rate of hydrogen is (0.2 to 0.8):1, and reacting for 0.5 h to 1.5 h to obtain a first reactant; S120, heating the first reactant to 250° C. to 350° C., wherein the flow rate of hydrogen is 0.5 L / min to 2.0 L / min, and the ratio of the flow rate of argon to the flow rate of hydrogen is (0.5 to 1):1, and reacting for 0.5 h to 2 h to obtain a second reactant; S130, heating the second reactant to 350° C. to 550° C., wherein the flow rate of hydrogen is 0.5 L / min to 1.2 L / min, and the ratio of the flow rate of argon to the flow rate of hydrogen is (0.8 to 1.2):1, and reacting for 0.5 h to 1.5 h to obtain a third reactant; S140, heating the third reactant to 450°C~900°C, at which time the flow rate of hydrogen is 0.1L / min~0.5L / min, and the ratio between the flow rate of argon and the flow rate of hydrogen is (2~4):1, and the first mixture is obtained after the reaction is carried out for 0.5h~1.5h.
3. The preparation method according to claim 1, characterized in that The step S300 further includes: S310, grinding the second mixture in an argon atmosphere to obtain a first crushed product having a size no greater than 80 μm; S320, placing the first crushed product in an argon flow at a temperature of 150° C. to 200° C. and a flow rate of 100 m / s to 500 m / s for jet milling to obtain a second crushed product; S330 , re-transporting the products with a size greater than 60 μm in the second crushed products to the second mixture in step S200 through a cyclone separator, and the products with a size less than or equal to 60 μm are the third mixture.
4. The preparation method according to claim 1, characterized in that The metal reducing agent is a hydride of an active metal; the active metal is one or more of potassium, calcium, sodium and magnesium.
5. The preparation method according to claim 1, characterized in that The step S400 further includes: S410, in an argon atmosphere, adding a buffer material and grinding balls to the third mixture, wherein the grinding ball rotation speed is 150 rpm to 350 rpm, the spheroidization temperature is ≤ 40° C., and the spheroidization time is 1 hour to 4 hours to obtain a third crushed product; S420, heating the third crushed product to 500° C. to 900° C. in an argon atmosphere to obtain a fourth reactant; S430. In an argon atmosphere, the fourth reactant is placed in a dilute hydrochloric acid solution for washing. The washing treatment temperature is 10° C. to 60° C., and the washing treatment time is 5 min to 10 min. The fourth mixture is obtained after drying.
6. The preparation method according to claim 5, characterized in that The buffer material is a stearic acid-nano calcium carbonate core-shell material, the mass ratio of the buffer material to the third mixture is (0.010-0.015):1, the mass ratio of the third mixture to the grinding balls is 1:(5.0-9.0), and the mass fraction of hydrogen chloride in the dilute hydrochloric acid is ≤5% (wt.%).
7. The preparation method according to claim 6, characterized in that The preparation method of the stearic acid-nano calcium carbonate core-shell material comprises the following steps: A100, ultrasonically treat the dried nano-calcium carbonate in anhydrous ethanol for 10 min to 30 min to obtain a first solution, and dissolve stearic acid in anhydrous ethanol and stir to form a second solution; A200, under alkaline conditions, adding the second solution to the first solution, heating and stirring, and separating to obtain a fifth mixture; A300, washing the fifth mixture with anhydrous ethanol and drying the mixture at a temperature of 50° C. to 80° C. to obtain a stearic acid-nano calcium carbonate core-shell material.
8. The preparation method according to claim 3, characterized in that The temperature of the grinding process in step S310 is ≤40°C.
9. The preparation method according to claim 1, characterized in that The step S500 further includes: performing a dehydrogenation treatment on the fourth mixture in a vacuum at 200° C. to 400° C. to obtain low-oxygen titanium.
10. A low-oxygen titanium, characterized in that: The invention is prepared by the preparation method according to any one of claims 1 to 9.
Citation Information
Patent Citations
Titanium-nitrogen alloy and preparation process thereof
CN103305710A
Method for directly preparing titanium alloy powder by using high titanium slag
CN111118308A
Method for producing titanium alloy product
CN115485403A
Method for preparing metal titanium powder through aluminum-magnesium gradient reduction of titanium dioxide
CN117086320A
Titanium alloy powder for additive manufacturing and preparation method thereof
CN118268561A